The causal effects of increased learning intensity on student achievement: Evidence from a natural experiment - Vincenzo Andrietti (Universidad Carlos III, 2015)
I exploit a unique educational policy - implemented in most German states between 2001 and 2007 - that reduced high school duration by one year while keeping its curriculum unaltered to investigate how the resulting increase in learning intensity affected student achievement. Using 2000-2009 PISA data and a difference-in-differences approach, I find robust evidence that the reform significantly improved the reading, mathematics, and science literacy skills acquired by academic-track high school students upon treatment. A more direct estimate of the effects of the increased learning intensity - as measured by the cumulative weekly number of instructional hours delivered in high school grades - corroborates the latter finding. Furthermore, there is some evidence that the effects of the reform differ by gender and grade retention. Finally, I find no evidence of a significant average effect of the reform on high school grade retention, although I do find that the latter increased significantly for boys and for students with a migration background.
Keywords: I21; I28; D04; 330; G8; Learning intensity; Instructional hours; Student achievement; Academic-track high school; Difference-in-Differences